The Response of Citronella Grass on Several NPKMg Fertlization Levels in Latosol Soil Type - Setiawan, NFN; Gusmaini, NFN; Nurhayati, Hera (Buletin Penelitian Tanaman Rempah dan Obat, 2018)
Citronella grass (Cymbopogon nardus var genuinus L) is an essential oil-producing plant known as "Citronella Oil of Java". Oil is resulted from leaf distillation. The fertilization of N, P, K and Mg was expected to enhance herb productivity and oil yield of citronella grass. The research was conducted at Cicurug Experimental Garden, Sukabumi from August 2016 - February 2017. The objective of this research was to determine the proper dosage of NPKMg fertilizer on citronella grass in Latosol soil type. The study was arranged in a Randomized Block Design with 6 fertilization treatments and 4 replications. Fertilizer treatments were (1) without fertilizer (control), (2) NPKMg (12:12:17:2): (2) at the dosage of 141 kg.ha-1,(3) 281 kg.ha-1, (4) 421 kg.ha-1, (5) 526 kg.ha-1, and (6) Urea 150 kg.ha-1, SP-36         50 kg.ha-1 and KCl 125 kg.ha-1 (as comparison). The NPKMg fertilization on citronella grass enhanced plant growth and increased the productivity of biomass and oil yield.  The application of NPKMg fertilization (12:12:17:2) 141 kg.ha-1 produced 23 tons of herbs, increased by 30.8 % compared to NPK fertilization without Mg. The dosage of NPKMg fertilizer (12-12-17-2) at 281 kg.ha-1 indicated the best growth and the highest herb production (24 ton.ha-1), increased by 39 %, while the highest oil content (1.4 %) was shown by 421 kg.ha-1 NPKMg (12-12-17-2) treatment, although the oil yield was insignificant compared to 281 kg.ha-1. Thus, the dosage of 281 kg.ha-1 NPKMg (12:12:17:2) can be recommended for citronella  grass cultivated at Latosol soil type